CONTRARREFORMAS EM TEMPOS DE INCERTEZAS: como fica a vida das mulheres? - Marly de Jesus Sá Dias (Universidade Federal do Maranhão, 2018)
The article provides considerations on the labor and Social Security counter-reform, in the context of neoliberalism, with a view to apprehending its impacts on women’s lives. Based on theoretical and documentary contributions, the logic contained in the proposal of some Constitutional Amendment Projects and Law Projects in the current political moment of the country is highlighted, with a view to the deconstruction of historical, universal guarantees in the Consolidation of Labor Laws, social security and public health. Social and political setbacks that threaten the dignity of the working class, with serious aggravation for women and that challenges social movements, such as feminists. It is concluded that a profound renewal of the meaning of collective actions, new structures of participation are necessary for the defense of social rights essential to human life and as a duty of the State.